IMPLEMENTATION OF A SECURITY SYSTEM WITH LASER SENSORS AND ARDUINO NANO AS MAIN CONTROL - Danang Novianto; Padulloh (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Implementation of a Security System with Laser Sensors and Arduino Nano as Main Control is an innovation that combines laser sensor technology with Arduino Nano control intelligence to increase the security level of a certain area. This system is designed to detect unwanted intrusion or penetration using strategically installed laser sensors. Laser sensors function as perimeter monitors, measuring and monitoring changes in light caused by the movement of surrounding objects. The information obtained from the laser sensor is then transmitted to the Arduino Nano as the main control. The Arduino Nano acts as the brain of the system, analyzing data received from laser sensors and making decisions based on pre- programmed security algorithms. In an intrusion detection situation, the Arduino Nano will activate a user-defined security response, such as activating an alarm, sending a notification to the user's device, or connecting to a broader security system. This system provides a security solution that is smart, responsive, and can be integrated with other systems. The implementation of this security system with laser sensors and Arduino Nano can be implemented in various environments, including homes, offices,or industrial areas that require additional layers of security. The advantage of this system lies in its ability to detect movement with high accuracy and respond quickly, providing effective protection against potential security threats.